LITERATURE REVIEW: STUDY OF LEARNING INDEPENDENCE IN REACTION RATE MATERIAL - Anggun Khanipah; Shil Hidayati (BIOCHEPHY: Journal of Science Education, 2025)
This study aims to examine and analyze the influence of learning autonomy on students' academic achievement in the topic of reaction rate through a literature review approach. Learning autonomy refers to students' ability to manage their own learning processes independently, without relying on others- particularly in understanding abstract and complex chemistry topics such as reaction rates. The review is based on ten peer-reviewed scientific articles published between 2019 and 2024, analyzed using a narrative synthesis method to interpret previous research findings. The results indicate that learning autonomy has a positive and significant relationship with students' academic achievement. Students with a high level of autonomy tend to be more active, show greater initiative, manage their time and learning strategies effectively, and achieve better academic outcomes. Therefore, fostering autonomous learning should be a central focus in instructional practices to enhance students' understanding and academic performance, especially in learning chemistry concepts like reaction rates.